(untitled) (Takwil: Journal of Quran and Hadith Studies, 2025)
The phenomenon of fatherlessness in society is not only caused by father who absents physically, but also psychologically absence in the development of their children. Children raised with the absence of paternal role tend to face psychological challenges, which may prevent their ability to develop their idemtity and the capacity to establish healthy social relationship. A father who serves as qawwam in the family, is expected to protect, educate, and responsible towards his family, especially to play role to educate their children. This study is aimed to examine how Mutawalli Asy-Sya’rawi interprets the concept of qawwam, as well as to discuss how Asy-Sya’rawi view of the qawwam relates to the phenomenon of fatherlessness. This research is classified as qualitative research with a descriptive-analytical method. The approaches used are tafsir maudhu’i and conceptual approach. The data used in this study is devided into primary, secondary, and tertiary that collected trough the library research methods. The results show that Asy-Sya’rawi defines a qawwam not only as a leader, caretaker, and protector, but also as an educator within the family. The concept of qawwam is not limited into a form of male domination towards his wife, but also includes a father’s responsibility towards his children, and an brother’s responsibility towards his sister. A father who fulfills his role as a qawwam with full of awareness to his accountability to Allah will also contribute to the children’s education, thereby reducing the likehood of the childrens experiencing a fatherless situation. The role of qawwam is not limited to the biological father, because if the father has passed away, his role can be replaced by the grandfather or parental uncle, just as Prophet Muhammad, who, although born as an orphan, was not in a fatherless situation because he was cared for by his grandfather and uncle